Relationship between trauma exposure, posttraumatic growth and posttraumatic stress disorder - Kazlauskas, Evaldas; Šimėnaitė, Irma; Gailienė, Danutė (Psichologija, 2007)
Objectives: The notion that traumatic experiences may have an impact on the human mind is very old. Recent developments in psychotraumatology shifted the approach to a trauma from a purely negative to a more positive perspective. Research confirmed that traumatic events may lead not only to posttraumatic stress or other disorders but also to positive changes. The present research was based on the concept of Posttraumatic Growth developed by Calhoun and Tedeschi (1996), which is widely known in the field of traumatic stress. Although the number of Posttraumatic Growth (PTG) research is growing rapidly, little is known about Posttraumatic Growth predictors. The present research was designed to find out the links between Posttraumatic Growth, Posttraumatic Stress and initial reactions to the traumatic event. We set up two goals of the study: 1) evaluation of how initial traumatic reactions predict PTG, and 2) assessment of links between PTG and PTSD. Methods: A group of 104 university students exposed to at least one-lifetime traumatic event participated in the study. The average time gap between exposure to a traumatic event and the time of research was 43 months. The intensity of initial reactions to a traumatic event was measured using a 10-item self-rating inventory developed by the authors of the present study. The Subjective Traumatic Experience (STE) inventory consisted of items covering cognitive, emotional and physiological reactions to a traumatic event. Posttraumatic Growth was measured using the Posttraumatic Growth Inventory (PGI) developed by Tedeschi and Calhoun (1996). Previous research showed satisfactory psychometric properties of the Lithuanian version of PGI (Gailienė & Kazlauskas, 2005). Posttraumatic Stress Disorder was measured using the Lithuanian version of the Impact of Event Scale-Revised (IES-R). A recent validation of the IES-R on Lithuanian population showed its good psychometric properties (Kazlauskas et al., 2006). Results: Correlation analysis revealed positive correlations among all three variables – PTG, STE and PTSD. Path analysis with two path models from STE to PTG and from STE to PTSD provided an adequate fit to the data χ2(1) = 1.62; p = .20; RMSEA = .077; NFI = .95; CFI = 1.0. Subjective traumatic experiences predicted Posttraumatic Growth (β= .32; T = 3.35) and PTSD (β = .42; T = 4.62). The modified model with correlations between PTG and PTSD added provided an ideal fit, but changes of the model were not significant: χ2difference (1) = 1.62; p > .05. Path analysis was made using LISREL software. Conclusions: The most significant predictor of both PTSD, and PTG was the intensity of initial reactions to a traumatic experience. While we found a weak but significant correlation between PTG and PTSD, the Path analysis has revealed that PTG and PTSD are rather distinct posttraumatic processes, both predicted by a traumatic event.
Keywords: trauma; posttraumatic stress; posttraumatic growth